Normalization and emancipation: Analysis of the institutionalization of the mental disability - Martín Contino, Alejandro (Pensando Psicología, 2010)
We attempt to make some hypothesis and tentative conclusions about the current situation of the categorized disabled people, who attend institutions dedicated to the mental disability where they use medicalized and normalization treatments, based on the Medical-Individual Model. We analyze the chronicity of these treatments, the logic of power that occurs there, and the subjectivity in these conditions, which would allow to sustain the reproduction of Hegemonic Medical Model, making it diffi cult to open to alternatives that imply radical differences to it, proposing for this, the contribution from the Social Model, aimed at the emancipation of the group of people who are in situation of disability.